Interactions with COVID-19 content on social media: Outcomes of social media use on student KAPs - Tran, Jordan; Denmon, Jennifer (Journal of Student Research, 2022)
In two years, COVID-19 has seen drastic developments in the world stage, so knowledge, attitudes, and practices (KAPs) on the disease may likewise be changing with it, which is the exigence of this study. One objective of this study is to find if there is a difference in KAP between social media platforms by doing Kruskal-Wallis H tests. Another objective is to compare results with past literature from the beginning of the pandemic by doing a multiple linear regression (MLR) and comparing the results for shared survey questions. A convenience sample of 52 students from a high school in the U.S. was surveyed, finding that less of them saw COVID-19 vaccinations as effective when compared to other prevention measures (75% vs. ~85%), 32.7% incorrectly responded that asymptomatic people cannot spread the disease, and that social media is the predominant channel of information on COVID-19 for them. Compared to other studies, the sample was not as risk perceptive in their attitudes and had lower adherence to the preventive practices. The survey responses were further turned into KAP scores to be used in the H tests and MLR. These found no significant difference in KAP scores between Twitter, Tik Tok, Instagram, and YouTube users, and predicted that holding more knowledge on the disease will lead to more practices being taken, while attitudes predicted no significant impact on the number of practices taken. With these lapses in KAPs, more awareness efforts on COVID-19 should be directed to students at the school of study.